Klasterisasi K-Means dan Model Markowitz dalam Pembentukan Portofolio Optimal Saham Syariah - Muhammad Kildah Namariq (Lembaga Pengembangan Kinerja Dosen, 2025)
This research seeks to construct an optimal portfolio of Sharia-compliant stocks listed in the Jakarta Islamic Index (JII) by integrating the Markowitz model with K-Means clustering. The dataset comprises the daily closing prices of JII constituent stocks and the risk-free return of BI-rate for the period of June–October 2025. The analysis begins with calculating the mean of stock returns and its corresponding standard deviation to identify the characteristics of each stock. The Silhouette Index is employed to determine the most suitable number of clusters, which indicates that three clusters provide the best separation. A representative stock is then selected from each cluster based on the Sharpe Ratio, resulting in BRPT, ASII, and UNVR as the primary candidates for portfolio construction. The Markowitz model is subsequently applied to determine the optimal portfolio weights, yielding an allocation of 16.29% for BRPT, 70.80% for ASII, and 12.91% for UNVR. The performance evaluation shows that the optimal portfolio achieves a Sharpe Ratio of 0.232872, higher than the JII index value of 0.118273, indicating superior risk–return efficiency. These findings demonstrate that a hybrid approach combining K-Means clustering and Markowitz optimization can enhance investment decision-making for Sharia-compliant stocks.